Preparation method of flexible graphene heat-conducting cable with high heat-conducting property
By preparing a composite aerogel powder doped with silicon nitride nanowires and mixing it with polydopamine graphene oxide powder to form a flexible graphene film, the problems of high-frequency signal interference and efficient heat dissipation in new energy vehicle battery modules are solved, and the high thermal conductivity and electromagnetic shielding performance are improved. At the same time, the toughness of the flexible graphene heat-conducting cable is enhanced.
Patent Information
- Application Number
- CN202510978973.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-16
- Publication Date
- 2025-10-28
AI Technical Summary
Existing graphene heat-conducting cables in new energy vehicle battery modules face challenges such as high-frequency signal interference and efficient heat dissipation. Traditional brazing methods are insufficient to meet the requirements for high thermal conductivity and electromagnetic shielding.
By preparing composite aerogel powder doped with silicon nitride nanowires and mixing it with polydopamine graphene oxide powder to form a flexible graphene film, and then using vacuum brazing technology to connect it to an aluminum alloy connector, a vertically oriented three-dimensional thermally conductive network and electromagnetic shielding structure are constructed.
The thermal conductivity and electromagnetic shielding properties of the flexible graphene thermal cable have been improved, avoiding high-frequency signal interference and enhancing its toughness and durability when bent.
Abstract
Description
Technical Field
[0001] This invention belongs to the field of dissimilar material joining technology, and relates to a method for preparing a flexible graphene thermal conductive cable with high thermal conductivity. Background Technology
[0002] With the rapid development of the automotive industry towards electrification and intelligence, the power density and integration of automotive electronic systems have significantly increased, leading to increasingly severe thermal management issues. Efficient heat dissipation has become a core requirement for ensuring the reliability, safety, and long lifespan of automotive electronic equipment. Key components of new energy vehicles, such as battery modules, motor controllers, and on-board chargers, generate a large amount of heat during operation. For example, during high-rate discharge, the local temperature of lithium-ion batteries may exceed 50°C, easily triggering thermal runaway risks. However, the compact space within the automotive engine compartment limits the effectiveness of traditional heat dissipation solutions (such as metal heat sinks and air cooling) due to installation space and weight constraints. Against this backdrop, highly thermally conductive flexible graphene heat-conducting cables, as an innovative solution, have demonstrated significant potential in the field of automotive module heat dissipation due to their unique performance advantages.
[0003] Chinese invention patent application CN117206614B discloses a method for preparing a lightweight, flexible, and highly thermally conductive graphene heat-conducting cable. The flexible segment of the heat-conducting cable is composed of multiple layers of highly thermally conductive graphene films and protective copper foil. Both ends of the heat-conducting cable are brazed structures where the flexible segment is bonded to a thermally conductive metal connector. Tin-based solder is filled between the flexible segment and the thermally conductive metal connector. After assembly, the cable is placed in a vacuum brazing furnace and heated to the brazing temperature of the tin-based solder to obtain a complete heat-conducting cable.
[0004] In the above scheme, the graphene heat-conducting cable adopts a secondary brazing method, which has high thermal conductivity and can reduce the thermal stress of the joint.
[0005] In the application scenarios of new energy vehicle battery modules, it is necessary to avoid interference from high-frequency signals. The electromagnetic shielding of graphene heat-conducting cables is mainly based on reflection, which makes it difficult to absorb high-frequency electromagnetic waves. The reflected electromagnetic waves will be superimposed on the vehicle communication signals, causing interference at the same frequency. Summary of the Invention
[0006] The purpose of this invention is to provide a method for preparing a flexible graphene thermal conductive cable with high thermal conductivity. The method involves mixing composite powder and polydopamine graphene oxide powder to form a flexible graphene film, which is then assembled. This method has good anti-electromagnetic interference and thermal conductivity.
[0007] The objective of this invention can be achieved through the following technical solutions:
[0008] A method for preparing a flexible graphene thermal conductive cable with high thermal conductivity includes the following steps:
[0009] Step 1: A composite aerogel doped with silicon nitride nanowires was prepared by oxidation-reduction method. The aerogel was ground and pulverized to obtain composite aerogel powder. Ferric chloride hexahydrate was used as the iron source to prepare ferric hydroxide colloidal solution, which was then loaded onto the composite aerogel powder. The ferric hydroxide was reduced to iron(III) oxide by high-temperature calcination to obtain composite powder.
[0010] Step 2: Coating graphene oxide powder with the self-polymerization of dopamine hydrochloride to obtain polydopamine graphene oxide powder. Mix the composite powder, deionized water and polydopamine graphene oxide powder evenly to make a slurry. Coat the slurry onto the release film and dry to obtain a flexible graphene film.
[0011] Step 3: Cut and stamp 20 layers of flexible graphite film, coat the welding area, arrange tin-based brazing alloy in the interlayer and contact gap between the layers and aluminum alloy at the ends of the flexible graphite film, and then put them into a vacuum brazing furnace to obtain a flexible graphene heat-conducting cable with high thermal conductivity.
[0012] Furthermore, the preparation process of the composite aerogel powder is as follows:
[0013] Silicon nitride nanowires with a diameter of 100-600 nm and graphene oxide dispersion with a concentration of 4 mg / mL were added to a reaction vessel, and ascorbic acid was added. The mixture was homogenized for 30-40 min, ultrasonically dispersed for 30-40 min, and reacted at 65-70℃ for 3-4 h. The mixture was then filtered, washed, directionally frozen for 30-40 min, dried, and ground to obtain composite aerogel powder.
[0014] Furthermore, the ratio of silicon nitride nanowires, graphene oxide dispersion, and ascorbic acid is 40-50g: 2-2.5L: 5-7g.
[0015] Furthermore, the preparation process of the composite powder is as follows:
[0016] Ferric chloride hexahydrate and deionized water were added to a reaction vessel. Boiling deionized water was added dropwise at 500-700 r / min. The reaction was carried out at 100℃ for 2-3 min, and then cooled to room temperature to obtain a ferric hydroxide colloidal solution. A composite aerogel powder dispersion with a concentration of 2 mg / mL was added to the reaction vessel. The ferric hydroxide colloidal solution was added dropwise to the reaction vessel at 800-1000 r / min. The mixture was allowed to stand for 24-26 h, filtered, washed, and dried. The mixture was then calcined at 1000-1200℃ for 2-3 h under nitrogen protection and ground to obtain a composite powder.
[0017] Furthermore, the volume ratio of the composite aerogel powder dispersion to the ferric hydroxide colloidal solution is 800-1200:520-640.
[0018] Furthermore, the preparation process of polydopamine graphene oxide powder is as follows:
[0019] Graphene oxide powder and Tris buffer solution with a concentration of 10 mM and a pH of 8.5 were added to a reaction vessel and sonicated for 90-100 min. Dopamine hydrochloride was then added, and the mixture was stirred at 500-700 r / min for 20-22 h. After centrifugation at 6000 r / min for 15-20 min, the mixture was washed, dried, and ground to obtain polydopamine graphene oxide powder.
[0020] Furthermore, the ratio of graphene oxide powder, Tris buffer, and dopamine hydrochloride is 6-10g:3-5L:6-10g.
[0021] Furthermore, the preparation process of the flexible graphene film is as follows:
[0022] The composite powder and deionized water are added to the reactor and stirred at 500-700 r / min for 2-3 h. Then, polydopamine graphene oxide powder is added and ultrasonically dispersed for 1-2 h to obtain a slurry. The slurry is then coated onto the release film using an automatic coating machine and dried to obtain a flexible graphene film.
[0023] Furthermore, the ratio of composite powder, deionized water, and polydopamine graphene oxide powder is 32-40g: 32-40L: 32-50g.
[0024] Furthermore, the slurry thickness is 20-30 μm.
[0025] Furthermore, the vacuum degree of the vacuum brazing furnace is 10. -3 Pa·m 3 / s, heating time is 10-15min.
[0026] The beneficial effects of this invention are:
[0027] 1. The high thermal conductivity flexible graphene heat-conducting cable of this invention is made by mixing composite powder and polydopamine graphene oxide powder to form a flexible graphene film, which is then assembled with aluminum alloy. The iron oxide in the composite powder can be oriented and regular under a magnetic field to form an effective conductive path, so that the absorption of electromagnetic waves by the nano-iron oxide is dominant. The continuous orientation structure is conducive to improving the electromagnetic shielding performance of the flexible graphene heat-conducting cable. The silicon nitride nanowire guides the graphene sheets to be vertically aligned, which is conducive to building an anisotropic electromagnetic wave scattering channel and further exfoliation under the action of thermal expansion, reducing the accumulation between the sheets and making full use of the specific surface area of the sheets to improve the absorption efficiency of electromagnetic waves. The two work together to improve the electromagnetic shielding performance of the high thermal conductivity flexible graphene heat-conducting cable, so that it can avoid interference from high frequency signals.
[0028] 2. In this invention, silicon nitride nanowires and graphene oxide are directionally frozen, allowing the graphene oxide sheets to form a vertical arrangement. Then, iron(III) oxide is anchored onto the graphene oxide via electrostatic assembly, constructing a vertically oriented three-dimensional thermally conductive network, which is beneficial for improving thermal conductivity. Furthermore, polydopamine can fill the micro-defects in the graphene oxide powder, reducing phonon boundary scattering and improving in-plane thermal conductivity. During vacuum brazing, the tin-based solder melts and penetrates to the edge of the graphene. 2 In the carbon network, a coherent interface is formed, reducing contact thermal resistance. Multiple mechanisms work together to improve the high thermal conductivity of the flexible graphene thermal cable.
[0029] 3. In this invention, the catechol groups of polydopamine are bonded to the oxygen-containing functional groups on graphene oxide, which increases the interfacial compatibility between the two. The polydopamine-modified graphene oxide surface forms a micro-wrinkled structure, which can absorb energy through elastic deformation when bent, avoiding brittle fracture. In addition, the silicon nitride nanowires and graphene oxide composite form a gel state. The high modulus of silicon nitride can share the external load. Furthermore, iron oxide is embedded in the interlayer of graphene oxide through electrostatic assembly, which can suppress stress concentration, thereby improving the toughness of the flexible graphene heat-conducting cable with high thermal conductivity, allowing it to bend multiple times without breaking. Detailed Implementation
[0030] To further illustrate the technical means and effects of the present invention in achieving the intended purpose, the following detailed description of the specific implementation methods, features and effects of the present invention, in conjunction with preferred embodiments, is provided below.
[0031] Example 1: This example provides a method for preparing a flexible graphene thermal conductive cable with high thermal conductivity, including the following steps:
[0032] S1: 45g of silicon nitride nanowires with a diameter of 100-600nm and 2.2L of graphene oxide dispersion with a concentration of 4mg / mL were added to a reaction vessel, followed by 6g of ascorbic acid. The mixture was homogenized for 35min, ultrasonically dispersed for 35min, and reacted at 67℃ for 3.5h. After filtration, the mixture was washed 4 times with deionized water, directionally frozen with liquid nitrogen for 35min, freeze-dried for 49h, and then ground to obtain composite aerogel powder.
[0033] S2: Add 18g of ferric chloride hexahydrate and 130mL of deionized water to a reaction vessel. Add 450mL of boiling deionized water dropwise at 600r / min. React at 100℃ for 2min. Cool to room temperature to obtain a ferric hydroxide colloidal solution. Add 1L of a 2mg / mL composite aerogel powder dispersion to the reaction vessel. Add the ferric hydroxide colloidal solution dropwise to the reaction vessel at 900r / min. Let stand for 25h, filter, wash the precipitate 4 times with deionized water, vacuum dry to constant weight, and place in a tube furnace. Calcine at 1100℃ for 2.5h. Ferric hydroxide is reduced to iron(III) oxide at high temperature and uniformly anchored on the surface and between layers of the composite aerogel powder after electrostatic assembly. Grind to obtain the composite powder.
[0034] S3: Add 8g of graphene oxide powder and 4L of 10mM Tris buffer solution with pH 8.5 to the reaction vessel, sonicate for 95min, then add 8g of dopamine hydrochloride, stir at 600r / min for 21h, centrifuge at 6000r / min for 17min, wash 6 times with deionized water, freeze dry for 13h, grind to obtain polydopamine graphene oxide powder.
[0035] S4: Add 36g of composite powder and 36L of deionized water to the reactor and stir at 600r / min for 2.5h. Then add 41g of polydopamine graphene oxide powder and ultrasonically disperse for 1.5h to obtain a slurry. Use an automatic coating machine to coat a 25μm slurry onto the release film and dry at 55℃ for 13h to obtain a flexible graphene film.
[0036] S5: Twenty layers of flexible graphite film are cut and stamped. Titanium, molybdenum, and nickel films are successively deposited on the surfaces and sides of the welding areas at both ends of each flexible graphite film using magnetron sputtering. Aluminum alloy parts undergo alkaline degreasing, chemical cleaning, and surface electroplating with nickel. Tin-based brazing alloy is processed into ultra-thin foil. The 20 layers of flexible graphite film are then stacked, with tin-based brazing alloy placed between the layers at the ends of the flexible graphite film and in the contact gaps between the layers and the aluminum alloy. Finally, the entire assembly is placed in a vacuum brazing furnace and evacuated to a vacuum level of 10. -3 Pa·m 3 Heating for 12 minutes at a constant temperature (°C) yields a flexible graphene thermal conductive cable with high thermal conductivity.
[0037] Example 2: This example provides a method for preparing a flexible graphene thermal conductive cable with high thermal conductivity, including the following steps:
[0038] S1: Add 40g of silicon nitride nanowires with a diameter of 100-600nm and 2L of graphene oxide dispersion with a concentration of 4mg / mL to a reaction vessel, then add 5g of ascorbic acid, homogenize for 30min, ultrasonically disperse for 30min, react at 65℃ for 3h, filter, wash 3 times with deionized water, directionally freeze-dry with liquid nitrogen for 30min, freeze-dry for 48h, grind and pulverize to obtain composite aerogel powder.
[0039] S2: Add 16g of ferric chloride hexahydrate and 120mL of deionized water to a reaction vessel. Add 400mL of boiling deionized water at 500r / min. React at 100℃ for 2min. Cool to room temperature to obtain a ferric hydroxide colloidal solution. Add 0.8L of a composite aerogel powder dispersion with a concentration of 2mg / mL to the reaction vessel. Add the ferric hydroxide colloidal solution to the reaction vessel at 800r / min. Let stand for 24h. Filter. Wash the precipitate three times with deionized water. Vacuum dry to constant weight and place in a tube furnace. Calcine at 1000℃ for 2h. Using some graphene as a reducing agent, ferric hydroxide is reduced to iron(III) oxide at high temperature and uniformly anchored on the surface and between layers of the composite aerogel powder after electrostatic assembly. Grind to obtain the composite powder.
[0040] S3: Add 6g of graphene oxide powder and 3L of 10mM Tris buffer solution with pH 8.5 to the reaction vessel, sonicate for 90min, then add 6g of dopamine hydrochloride, stir at 500r / min for 20h, centrifuge at 6000r / min for 15min, wash 5 times with deionized water, freeze dry for 12h, grind to obtain polydopamine graphene oxide powder.
[0041] S4: Add 32g of composite powder and 32L of deionized water to the reactor and stir at 500r / min for 2h. Then add 32g of polydopamine graphene oxide powder and ultrasonically disperse for 1h to obtain a slurry. Use an automatic coating machine to coat a 20μm slurry onto the release film and dry at 50℃ for 12h to obtain a flexible graphene film.
[0042] S5: Twenty layers of flexible graphite film are cut and stamped. Titanium, molybdenum, and nickel films are successively deposited on the surfaces and sides of the welding areas at both ends of each flexible graphite film using magnetron sputtering. Aluminum alloy parts undergo alkaline degreasing, chemical cleaning, and surface electroplating with nickel. Tin-based brazing alloy is processed into ultra-thin foil. The 20 layers of flexible graphite film are then stacked, with tin-based brazing alloy placed between the layers at the ends of the flexible graphite film and in the contact gaps between the layers and the aluminum alloy. Finally, the entire assembly is placed in a vacuum brazing furnace and evacuated to a vacuum level of 10. -3 Pa·m 3Heating for 10 minutes at a constant temperature ( / s) yields a flexible graphene thermal conductive cable with high thermal conductivity.
[0043] Example 3: This example provides a method for preparing a flexible graphene thermal conductive cable with high thermal conductivity, including the following steps:
[0044] S1: Add 50g of silicon nitride nanowires with a diameter of 100-600nm and 2.5L of graphene oxide dispersion with a concentration of 4mg / mL to a reaction vessel, then add 7g of ascorbic acid, homogenize for 40min, ultrasonically disperse for 40min, react at 70℃ for 4h, filter, wash 5 times with deionized water, directionally freeze-dry with liquid nitrogen for 40min, freeze-dry for 50h, grind and pulverize to obtain composite aerogel powder.
[0045] S2: Add 20g of ferric chloride hexahydrate and 140mL of deionized water to a reaction vessel. Add 500mL of boiling deionized water dropwise at 700r / min. React at 100℃ for 3min. Cool to room temperature to obtain a ferric hydroxide colloidal solution. Add 1.2L of a composite aerogel powder dispersion with a concentration of 2mg / mL to the reaction vessel. Add the ferric hydroxide colloidal solution dropwise to the reaction vessel at 1000r / min. Let stand for 26h, filter, wash the precipitate 5 times with deionized water, vacuum dry to constant weight, and place in a tube furnace. Calcine at 1200℃ for 3h. Ferric hydroxide is reduced to iron(III) oxide at high temperature and uniformly anchored on the surface and between layers of the composite aerogel powder after electrostatic assembly. Grind to obtain the composite powder.
[0046] S3: Add 10g of graphene oxide powder and 5L of 10mM Tris buffer solution with pH 8.5 to the reaction vessel, sonicate for 100min, then add 10g of dopamine hydrochloride, stir at 700r / min for 22h, centrifuge at 6000r / min for 20min, wash with deionized water 7 times, freeze dry for 14h, grind to obtain polydopamine graphene oxide powder.
[0047] S4: Add 40g of composite powder and 40L of deionized water to the reactor and stir at 700r / min for 3h. Then add 50g of polydopamine graphene oxide powder and ultrasonically disperse for 2h to obtain a slurry. Use an automatic coating machine to coat a 30μm slurry onto the release film and dry at 60℃ for 14h to obtain a flexible graphene film.
[0048] S5: Twenty layers of flexible graphite film are cut and stamped. Titanium, molybdenum, and nickel films are successively deposited on the surfaces and sides of the welding areas at both ends of each flexible graphite film using magnetron sputtering. Aluminum alloy parts undergo alkaline degreasing, chemical cleaning, and surface electroplating with nickel. Tin-based brazing alloy is processed into ultra-thin foil. The 20 layers of flexible graphite film are then stacked, with tin-based brazing alloy placed between the layers at the ends of the flexible graphite film and in the contact gaps between the layers and the aluminum alloy. Finally, the entire assembly is placed in a vacuum brazing furnace and evacuated to a vacuum level of 10. -3 Pa·m 3 Heating for 15 minutes at a constant temperature (°C) yields a flexible graphene thermal conductive cable with high thermal conductivity.
[0049] Comparative Example 1: Based on Example 1, in step S4, the composite aerogel powder prepared in step S1 was used instead of the composite powder, while the other steps remained unchanged, and a flexible graphene film was prepared.
[0050] Comparative Example 2: Based on Example 1, in step S4, graphene oxide powder was used instead of polydopamine graphene oxide powder, while the other steps remained unchanged, and a flexible graphene film was prepared.
[0051] Comparative Example 3: Based on Example 1, the composite powder was removed in step S4, while the other steps remained unchanged, and a flexible graphene film was prepared.
[0052] The flexible graphene films prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance testing:
[0053] Electromagnetic shielding performance: Referring to GJB 6190-2008 standard, the test frequency band is 8GHz-12.5GHz. The shielding ability of electromagnetic shielding materials against electromagnetic waves is called electromagnetic shielding effectiveness (SE), which can be expressed in decibels (dB). The calculation formula is as follows: SE=-10log(P T / P O SE represents electromagnetic shielding effectiveness, indicating the material's ability to shield electromagnetic waves. P T P is the power of the transmitted wave. O The power of the incident wave is denoted as .
[0054] Mechanical properties: Referring to national standard GB / T 1040.3-2006, a CMT6103 universal testing machine was used. Before testing, the samples were cut into strips with a length of 25 mm and a width of 10 mm. The loading rate of the testing machine was 1 mm / min. The test data were analyzed using Origin 2019b software. The toughness of the sample was obtained by integrating the area enclosed by its corresponding stress-strain curve. Parallel tests were performed, and the final result was the average value of the tests.
[0055] Thermal conductivity: An unsteady-state method was used for testing. The instrument used was a laser thermal conductivity meter. A short laser pulse was emitted to heat the front of the sample. By monitoring the temperature at a certain location on the back, the relationship between temperature rise and time could be obtained. The thermal diffusivity could be calculated from the half-heating curve. Specific heat of the sample: The specific heat of the sample could be obtained by comparing it with that of sapphire, which has a known specific heat capacity. Density of the sample: This could be obtained using a simple physical method, namely the mass-volume method. The formula for calculating thermal conductivity is as follows: λ = α·ρ·C p In the formula: λ is the thermal conductivity of the sample (W / (mK)); α is the thermal diffusivity of the sample (m). 2 / s); ρ is the density of the sample (Kg / m³). 3 ); C p The constant-pressure specific heat capacity of the sample is (J / kg K).
[0056] The performance test results are shown in the table below:
[0057] Table 1 Performance Test Overview
[0058] project Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 SE(dB) 25 24 24 16 23 15 Tensile strength (MPa) 21.94 21.54 21.68 15.56 14.51 15.14 <![CDATA[Toughness (KJ / m -3 )]]> 75.2 75.1 74.9 51.2 45.29 47.53 Thermal conductivity (W / (mK)) 498.95 487.04 490.54 414.1 430.1 342.2
[0059] As shown in Table 1, the electromagnetic shielding effectiveness (SE) of Examples 1-3 is greater than that of Comparative Examples 1 and 3. In Comparative Example 1, the composite aerogel powder prepared in step S1 was used to replace the composite powder in step S4, while in Comparative Example 3, the composite powder was removed in step S4. This may be because the iron oxide in the composite powder can be oriented and regular under a magnetic field to form an effective conductive path, which makes the absorption of electromagnetic waves by the nano-iron oxide dominant. The silicon nitride nanowires guide the graphene sheets to be vertically aligned, improving the absorption efficiency of electromagnetic waves. The two work together to improve the electromagnetic shielding performance of the flexible graphene heat-conducting cable with high thermal conductivity.
[0060] The tensile strength and toughness of Examples 1-3 are all greater than those of Comparative Examples 1-3. In step S4 of Comparative Example 1, the composite aerogel powder prepared in step S1 is used instead of the composite powder. In step S4 of Comparative Example 2, graphene oxide powder is used instead of polydopamine graphene oxide powder. In step S4 of Comparative Example 3, the composite powder is removed. This may be because the surface of polydopamine-modified graphene oxide forms a micro-wrinkled structure, which can absorb energy through elastic deformation when bent. The composite of silicon nitride nanowires and graphene oxide forms a gel state that can share the external load. Iron oxide is embedded in the interlayer of graphene oxide through electrostatic assembly, which can suppress stress concentration. Thus, the toughness of the flexible graphene heat-conducting cable with high thermal conductivity is improved.
[0061] The thermal conductivity of Examples 1-3 is greater than that of Comparative Examples 1-3. In step S4 of Comparative Example 1, the composite aerogel powder prepared in step S1 is used instead of the composite powder. In step S4 of Comparative Example 2, graphene oxide powder is used instead of polydopamine graphene oxide powder. In step S4 of Comparative Example 3, the composite powder is removed. This may be because the silicon nitride nanowires and graphene oxide are oriented and frozen, allowing the graphene oxide sheets to form a vertical arrangement. Then, iron oxide is anchored on the graphene oxide to construct a vertically oriented three-dimensional thermally conductive network. Polydopamine can fill the micro-defects in the graphene oxide powder, reduce phonon boundary scattering, improve in-plane thermal conductivity, and improve the thermal conductivity of the flexible graphene thermal cable.
[0062] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A method for preparing a flexible graphene thermally conductive cable with high thermal conductivity, characterized in that, The steps include: Step 1: A composite aerogel doped with silicon nitride nanowires was prepared by oxidation-reduction method. The aerogel was ground and pulverized to obtain composite aerogel powder. Ferric chloride hexahydrate was used as the iron source to prepare ferric hydroxide colloidal solution, which was then loaded onto the composite aerogel powder. The ferric hydroxide was reduced to iron(III) oxide by high-temperature calcination to obtain composite powder. Step 2: Coating graphene oxide powder with the self-polymerization of dopamine hydrochloride to obtain polydopamine graphene oxide powder. Mix the composite powder, deionized water and polydopamine graphene oxide powder evenly to make a slurry. Coat the slurry onto the release film and dry to obtain a flexible graphene film. Step 3: Cut and stamp 20 layers of flexible graphite film, coat the welding area, arrange tin-based brazing alloy in the interlayer and contact gap between the layers and aluminum alloy at the ends of the flexible graphite film, and then put them into a vacuum brazing furnace to obtain a flexible graphene heat-conducting cable with high thermal conductivity.
2. The method for preparing a flexible graphene thermal conductive cable with high thermal conductivity according to claim 1, characterized in that, The preparation process of the composite aerogel powder in step one is as follows: Silicon nitride nanowires with a diameter of 100-600 nm and graphene oxide dispersion with a concentration of 4 mg / mL were added to a reaction vessel, and ascorbic acid was added. The mixture was homogenized for 30-40 min, ultrasonically dispersed for 30-40 min, and reacted at 65-70℃ for 3-4 h. The mixture was then filtered, washed, directionally frozen for 30-40 min, dried, and ground to obtain composite aerogel powder.
3. The method for preparing a flexible graphene thermally conductive cable with high thermal conductivity according to claim 2, characterized in that, The ratio of silicon nitride nanowires, graphene oxide dispersion, and ascorbic acid is 40-50g: 2-2.5L: 5-7g.
4. The method for preparing a flexible graphene thermally conductive cable with high thermal conductivity according to claim 1, characterized in that, The preparation process of the composite powder in step one is as follows: Ferric chloride hexahydrate and deionized water were added to a reaction vessel. Boiling deionized water was added dropwise at 500-700 r / min. The reaction was carried out at 100℃ for 2-3 min, and then cooled to room temperature to obtain a ferric hydroxide colloidal solution. A composite aerogel powder dispersion with a concentration of 2 mg / mL was added to the reaction vessel. The ferric hydroxide colloidal solution was added dropwise to the reaction vessel at 800-1000 r / min. The mixture was allowed to stand for 24-26 h, filtered, washed, and dried. The mixture was then calcined at 1000-1200℃ for 2-3 h under nitrogen protection and ground to obtain a composite powder.
5. The method for preparing a flexible graphene thermal conductive cable with high thermal conductivity according to claim 4, characterized in that, The volume ratio of the composite aerogel powder dispersion to the ferric hydroxide colloidal solution is 800-1200:520-640.
6. The method for preparing a flexible graphene thermally conductive cable with high thermal conductivity according to claim 1, characterized in that, The preparation process of the polydopamine graphene oxide powder in step two is as follows: Graphene oxide powder and Tris buffer solution with a concentration of 10 mM and a pH of 8.5 were added to a reaction vessel and sonicated for 90-100 min. Dopamine hydrochloride was then added, and the mixture was stirred at 500-700 r / min for 20-22 h. After centrifugation at 6000 r / min for 15-20 min, the mixture was washed, dried, and ground to obtain polydopamine graphene oxide powder.
7. The method for preparing a flexible graphene thermally conductive cable with high thermal conductivity according to claim 6, characterized in that, The ratio of graphene oxide powder, Tris buffer solution, and dopamine hydrochloride is 6-10g: 3-5L: 6-10g.
8. The method for preparing a flexible graphene thermally conductive cable with high thermal conductivity according to claim 1, characterized in that, The preparation process of the flexible graphene film in step two is as follows: The composite powder and deionized water are added to the reactor and stirred at 500-700 r / min for 2-3 h. Then, polydopamine graphene oxide powder is added and ultrasonically dispersed for 1-2 h to obtain a slurry. The slurry is then coated onto the release film using an automatic coating machine and dried to obtain a flexible graphene film.
9. The method for preparing a flexible graphene thermally conductive cable with high thermal conductivity according to claim 8, characterized in that, The ratio of the composite powder, deionized water, and polydopamine graphene oxide powder is 32-40g:32-40L:32-50g; the slurry thickness is 20-30μm.
10. The method for preparing a flexible graphene thermally conductive cable with high thermal conductivity according to claim 1, characterized in that, The vacuum degree of the vacuum brazing furnace is 10. -3 Pa·m 3 / s, heating time is 10-15min.
Citation Information
Patent Citations
A method for preparing a lightweight, flexible, high-thermal-conductivity graphene thermal cable
CN117206614B